Maternal Mortality Evaluation: A Case Study in Bantul, Yogyakarta - Dewi, Arlina; Bekti, Nikma Kurnianingtyas; Supriyatiningsih, Supriyatiningsih (Journal of Maternal and Child Health, 2019)
Background: Maternal mortality rate is one of the indicators to measure the level of a woman's health. The maternal mortality rate in Indonesia is still high, it's about 190/100.000 live birth. The objective of the present study is to evaluate the cause of maternal death in Bantul at 2016 which related to the health services including human resources. Subjects and Method: This was a mixed method with case study design on maternal mortality in Bantul District. The qualitative data collected through Focus Group Discussion (FGD) and the quantitative data from the questionnaire were filled by a senior midwife throughout the hospital in Bantul. The number of hospitals in Bantul District was 11 consisting of 1 government hospital and 10 private hospitals. Results: The number of obstetricians who could be available 24 hours in hospitals was still limited. The skills of midwives were still considered to be limited in handling a number of obstetric emergency conditions due to the lack of regular training. The primary health care services which had been provided to support and handle obstetric emergencies, but the infrastructure and human resources were still considered inadequate. Thus, there was also a condition where the utilization of integrated ANC facilities in the primary health center (Puskesmas) was still low, soan early detection of complications of pregnancy was less optimal. Conclusion: There are three main topics causing the maternal mortality at Bantul, and those are 1)Maternal mortality related to hospital facilities, 2) Maternal mortality related to human resources at the hospital, 3) Maternal mortality related to health center facility. Keywords: maternal, obstetrician stand-by, hospital Correspondence: